Physical Education Intructional Models in Volleyball Passing Material: A Literature Review - Arifin, Bustanul; Hasan, Nurhasan; Tuasikal, Abdul Rachman Syam (Prodi PGSD Penjas FPOK UPI, 2021)
Intructional model in Physical Education becomes an important part to achieve the success of learning objectives at every level of education. Physical Education intructional model consists of various models that can be applied by the teacher. The intructional model carried out will affect a student mastery, including in passing technique learning in volleyball that has not got maximum results. Physical Education teachers implement several learning modifications, from teaching style to the use of supporting media for passing learning. The purpose of this study was to determine the most suitable intructional model for the under passing technique mastery in volleyball. The literature review technique was employed by collecting literatures from google scholar, science direct, and research gate websites. The search keyword was passing intructional model in volleyball or volleyball teaching models. The review method was chosen to find a solution related to the most appropriate volleyball intructional model for passing technique from the findings of previous research. Fourteen national journals and 1 international journal were selected based on volleyball passing learning model keyword on google scholar and had been reviewed. The results showed that there are various learning methods applied in volleyball passing learning, including practical learning models with various movement drills, pair practice, cooperative learning, game learning, jigsaw, discovery learning, peer teaching, command learning, and use of walls as media. This study concludes that, in the volleyball passing mastery, there are various models that can be applied. It recommends that further research studies the most suitable practical learning models to be applied at the Elementary School, Junior High School, and Senior High School levels.